(untitled) (Encuentros, 2023)
The research problem was to show that currently, the non-use of ICT resources in mathematics education can become a unequivocal action. The objective; Characterize mathematical technological knowledge and its relationship with virtual learning environments of mathematics teachers in training. The research, of a quais litative type under a multiple case study approach. The methodology, was devloped through three phases. The main results found showed the little training received by future mathematics teachers under VAS of learning. The proposed contributions are aimed at contributing to future research, providing a reflective point of view regarding the training received daily by teachers in mathematics.